Pengaruh Esktrak Daun Krokot (Portulaca Oleracea) Terhadap Kadar Gula Darah Pada Tikus Yang Diinduksi Aloksan - Sukma Sahreni; Kasih Purwati; Dicky Pratama (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2022)
Background: Diabetes mellitus (DM) is a degenerative disease caused by damage to the pancreas in production or insulin cannot work effectively. Purslane Leaf Extract (Portulaca Oleracea) can help lower blood sugar levels. The purpose of this study was to analyze the effect of purslane leaf extract (Portulaca Oleracea) on blood sugar levels in alloxan-induced rats as a diabetes model.Methods: The rats in this study were 30 rats divided into 5 groups, each group consisting of 6 rats. The negative control group was only given aquadest and standard rat feed, while the other group was induced with 35 mg/200gBW of alloxan. The positive group was treated with standard rat diet, treatment group 1 was given purslane leaf extract at a dose of 60 mg/200grBB, treatment group 2 was given purslane leaf extract at a dose of 90 mg/200grBB and treatment group 3 was given purslane leaf extract at a dose of 110 mg/200grBW rats. Analysis of the results used the Kruskall Wallis test followed by Post Hoc Mann Whitney analysis. Results: The results of the Kruskal Wallis test on blood sugar levels showed that there was an effect after administration of purslane leaf extract among the five treatment groups p= 0.000 (p<0.05). The results of the Mann Whitney test showed that purslane leaf extract had effective antidiabetic at a dose 60 mg/200grBB p= 0.011 (p<0.05).Conclusion: Based on the results of this study, it can be concluded that purslane leaf extract can reduce blood sugar levels.